Development Model of People’s Business Credit Impact on MSME Productivity and Sustainability - Wuri Septi Handayani; Rinny Meidiyustiani (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to analyze the impact of People’s Business Credit (KUR) distribution on MSME productivity and business sustainability among women-owned MSMEs in Tangerang City. Design/methodology/approach – This study uses quantitative and qualitative approaches. Data were collected through questionnaires and interviews with 90 women MSME actors. The data were analyzed using descriptive statistics and structural modeling with SmartPLS. Finding/Results – The results show that KUR distribution has a positive and significant influence on MSME productivity and business sustainability. Productivity also significantly influences business sustainability. Originality/Value – The study provides a model explaining how access to credit improves productivity and supports the long-term sustainability of MSMEs.